Silicate-modified oiltea camellia shell-derived biochar: A novel and cost-effective sorbent for cadmium removal. (25th January 2021) - Cai, Tong; Liu, Xiaoli; Zhang, Jiachao; Tie, Baiqing; Lei, Ming; Wei, Xiangdong; Peng, Ou; Du, Huihui
Abstract: Oiltea camellia shells are a substantial agricultural waste in southern China, but their resource utilization has not been given due attention. In this study, we prepared oiltea camellia shell biochar by pyrolysis (500 °C) in the presence of sodium silicate, and investigated its adsorption capacity for Cd removal. The SEM characterization shows that silicon (Si) is loaded on biochar surfaces as fine particles, and are identified as quartz (SiO2 ), silicate and C–Si mixture according to X-ray diffraction. Silicate-modification significantly increases (∼45–112%) specific surface area (SSA) and slightly increases (∼5–12%) porosity of biochar. Batch results reveal that Si-modification significantly enhances Cd adsorption, and this increment is more pronounced at pH > 5. Furthermore, silicate-modification promotes the internal diffusion of Cd on biochar. FTIR and XPS analyses suggest that ion exchange with Na +, surface precipitation (CdCO3, CdSiO3 or Cd2 SiO4 ), coordination with π electrons (CC) and complexation with carboxyl and C–Si–O groups are the predominant sorption mechanisms. This study puts a new perspective on the waste utilization of oiltea camellia shells for heavy metal removal from wastewaters or stabilization in contaminated soils. Graphical abstract: Image 1 Highlights: Na2 SiO3 modification improves porosity and functional groups on biochar surface. Na2 SiO3 modification significantly enhances Cd removal than raw biochar. Cd adsorption fits the Langmuir isotherm and pseudo-second-order kinetic model. Ion exchange, surface precipitation and complexation dominant Cd adsorption.